MDII (Multidimensional Digital Inclusiveness Index) - Martins, Carolina; Nisansa, Vinuri; Opola, Felix Ouko; Garcia Andarcia, Mariangel; Schmitter, Petra (International Water Management Institute, 2025)
The Multidimensional Digital Inclusivity Index (MDII) is a scientific framework developed by the International Water Management Institute (IWMI) and CGIAR to ensure digital solutions in agrifood systems are inclusive and equitable. Designed for the Global South, MDII evaluates tools across 90 indicators grouped into seven dimensions, covering accessibility, usability, social impact, and governance. It identifies barriers such as language, offline functionality, training gaps, and ethical safeguards, providing actionable recommendations to improve adoption among underrepresented groups such as women, the elderly, and those with limited education. Assessments conducted in 10 countries reveal that technical soundness alone does not guarantee inclusiveness; localization and community engagement are critical. MDII supports developers, researchers, and policymakers by offering evidence-based insights to embed inclusivity throughout the innovation lifecycle. Future enhancements include AI-driven rapid assessments and modules for gender and economic impact. By addressing structural and experiential aspects of digital adoption, MDII helps bridge the digital divide and promotes responsible, socially inclusive innovation in food, water, and land systems. Learn more or start an evaluation at https://mdii.iwmi.org.